Pelaksanaan sistem Kawalan Gelagat Di Institut-Institut Pendidikan Di Alor Setar - Noor Hayati, Abdullah (2000)

(untitled)
This qualitative research is carried out to identify the procedures that must be adhered to by school principals in ensuring that the behaviour control system in their respective schools are effective in maintaining good school climate. A sample of 16 educational institutions in Alor Setar was taken, with these institutions being fully-funded secondary schools managed by the Education Ministry. Data was collected through interviews on school Principals, Senior Assistants in charge of Academic and Student Affairs, and Discipline Teachers. Research instrument consisted of structured questions and percentage analyses were carried out on the data. Research findings showed all school discipline administrators being well versed with the procedures and guidelines as allowed for by the Education Ministry. All respondents agreed that the use of discretion is of utmost importance when deliberating on an offense by students, and that discretion should only be used when the offences are minor in nature. The research findings also noted that any controversies that may arise out of the use of discretion could usually be dispelled when proper explanation are given to the dissenting parties. The empowerment process as practised in the schools are also found to be properly administered as required by the Education Ministry. However, it was found that ordinary teachers who are not part of the school discipline administrators are the ones who lacked in understanding of the procedures and provisions before disciplinary actions can be carried out on students. This is where most problems occur because ordinary teachers are the ones who come most in contact with students yet they are the ones without proper undertstanding of the discipline procedures, resulting in improper actions sometimes carried out by them. Hence, as a conclusion, it could be said that the target groups that must be made aware and competent in disciplinary procedures are not just the upper echelon of school administration, but also and more importantly, the ordinary teachers who are the ones most susceptible to take discipline actions into their own hands. By malting these groups aware of the proper steps and actions to take, hopefully teachers will not take actions that are outside the provisions of the Education Ministry.